2009
DOI: 10.1007/s12042-009-9030-9
|View full text |Cite
|
Sign up to set email alerts
|

Carica papaya Genes Regulated by Phytophthora palmivora: A Model System for Genomic Studies of Compatible Phytophthora-plant Interactions

Abstract: Plant pathogenic Phytophthora species are predicted to encode a large arsenal of 'effector' proteins that target and disrupt normal host cell function, but genes regulated by effectors are difficult to distinguish from those more generally regulated by microbe associated molecular patterns (MAMPs). To help make this distinction, expression studies of host-Phytophthora interactions can be compared to reveal patterns of gene regulation indicative of effector activity. The recently sequenced tropical fruit tree, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Peroxidases (PR-9) are potential cross-species Phytophthora effector targets, since a certain C. papaya peroxidase (EL784270) and its putative orthologs have been suppressed in different hosts upon inoculation with P. sojae, P. palmivora , and P. infestans (Moy et al, 2004 ; Restrepo et al, 2005 ; Porter et al, 2009 ). An E. grandis gene, Eucgr.E04056, is highly similar to the C. papaya ortholog, and is also strongly suppressed in the current interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxidases (PR-9) are potential cross-species Phytophthora effector targets, since a certain C. papaya peroxidase (EL784270) and its putative orthologs have been suppressed in different hosts upon inoculation with P. sojae, P. palmivora , and P. infestans (Moy et al, 2004 ; Restrepo et al, 2005 ; Porter et al, 2009 ). An E. grandis gene, Eucgr.E04056, is highly similar to the C. papaya ortholog, and is also strongly suppressed in the current interaction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, P. infestans manipulates its host to suit its life-style by suppressing the hypersensitive response (HR) in potato during its biotrophic phase, then manipulating the induction of HR during the necrotrophic phase (Bos et al, 2010 ; Gilroy et al, 2011 ). This type of manipulation could be a trend in other Phytophthora interactions (Belhaj et al, 2009 ; Porter et al, 2009 ). Effectors excreted during this interaction are primarily crinklers (CRN), a family of proteins expressed in all plant pathogenic oomycetes, and RxLRs which are confined to only Phytophthora species (Stam et al, 2013b ; Chen et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 19 genes significantly up‐regulated in A. thaliana in response to P. parasitica infection, signature sequences characteristic of biotic stresses were notable. For example, a homologue of TC1736, which encodes a putative peroxidase, was identified to be up‐regulated in papaya challenged with P. palmivora (Porter et al ., 2009). The homologues of TC2158, TC2086 and TC1736 were reported to be up‐regulated by twofold or more in soybean infected with P. sojae (Moy et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other PR proteins such as peroxidases (PR9) were up- and down-regulated in P. pinea , similar to the interaction of P. pinaster - F. circinatum at 10 dpi [ 42 ] and Eucalyptus nitens - Phytophthora cinnamomi at 5 dpi [ 36 ]. This could point out pine PR9 as effector target of F. circinatum , which has been found in several Phytophthora species infecting Carica papaya [ 86 , 87 , 88 ]. It has been suggested that activation of PR genes, notably plant chitinases, is produced mainly in susceptible Pinus spp.…”
Section: Discussionmentioning
confidence: 98%